KORELASI MODEL KOMUNIKASI DEMOKRATIS DENGAN PEMANFAATAN LKPD BERBASIS INTERAKSI DI YAYASAN ALANG-ALANG CIAWI BOGOR - Agnesha, Nova; Atikah, Ike; Setiawan, Koesworo (JURNAL KOMUNIKATIO, 2020)
The most ideal model of parental communication to apply is the communication model of democratic parents. But in reality there are still many parents who do not understand the application of democratic communication model to their children. With democratic communication model, the development of children will develop well. This study aims to analyze the application of parental communication model in daily life to their children. The research approach used is quantitative This study discusses the application of communication model of democratic parents at the Alang-alang Foundation Ciawi Bogor , the method used descriptive quantitative method. The research sample was carried out to parents of participants consisting of 41 people. The results of the study show that (1) affection and understanding are very good (2) strict and consistent discipline is in good category, (3) freedom of opinion in good category, (4) discussion in good category, (5) respecting good categories, ( 6) Understanding is categorized well. Keywords: communication model, parent, democratic